On the Global Phenomenon of Rights of Nature from a European Environmental Law Perspective A New Alliance with Nature - Tahyné Kovács Ágnes (Teremtésvédelem, 2025)
In an era where ecological crises—deforestation, polluted waters, and climate upheaval—demand urgent attention, Rights of Nature and Creation Care offers a nuanced exploration of a transformative legal and ethical concept: the Rights of Nature. This book does not advocate for blindly adopting this framework but seeks to deepen understanding of its principles, origins, and potential within the context of environmental law and the Catholic Church’s teachings on creation care. The Rights of Nature represents a bold shift in environmental thought, emerging over the past fifty years, to grant legal personhood and inherent rights to ecosystems, rivers, forests, and species—rights to exist, flourish, and regenerate free from excessive human harm. Rooted in traditions outside Europe’s Roman law systems, this concept challenges conventional legal paradigms by recognizing nature’s intrinsic value, distinct from its utility to humans. Through global examples, such as New Zealand’s Whanganui River, granted legal status, or Ecuador’s constitutional protections for Pachamama, the book illuminates diverse approaches to this idea and examines how it might resonate within European legal and cultural frameworks. To interpret the phenomenon, we will also highlight some elements of the social teaching of the Catholic Church that reflect on the relationship between the created world and man. Although the church does not interpret the Rights of Nature phenomenon, the message of many teaching elements carries respect for nature. The volume does not aim to conduct an examination of theological teachings in the area of the rights of nature, but rather to highlight those elements of the church's social teaching that help us think about the phenomenon.This volume invites legal scholars, policymakers, theologians, and concerned readers to engage with the Rights of Nature as a concept worth understanding. By blending rigorous legal analysis with theological insights, Rights of Nature and Creation Care fosters informed dialogue about reimagining humanity’s relationship with the natural world, encouraging reflection on how legal and spiritual frameworks can together address our shared ecological responsibilities.